POTENSI KARBON TANAH DI BAWAH TEGAKAN SENGON (PARASERIANTHES FALCATARIA L) PADA AREAL IPKH PT. SARI BUMI KUSUMA DESA KUALA DUA KABUPATEN KUBURAYA - Perawati, Pera; Hardiansyah, Gusti; Idham, M (JURNAL HUTAN LESTARI, 2015)
This research objectives is to estimate the amount of pool carbon ( below ground and abone ground) under the sengon (Paraserianthes falcataria L) stand groun at aluvial and peat land in the area of wood processing industry forest plywood PT. Sari Bumi Kusuma.Methodelogy applied four carbon stock soil sampel is to make 4 plot size 0,5x0,5 m2 under the stand of sengon composite mixing plet soil sampel 30 cm depith every plot. Were analyzed the result of carbon stock in the soil of aluvial land is 31,3 g/cm2 and 467,28 g/cm2 in the soil of peat land. Estimate the biomass above ground (ABG) of Sengon (Paraserianthes falcataria L) stands using allometrick Y =0,00272D 2,831, the result for aluvial land 153,34 kg/pohon and peat land 192,58 kg/pohon. Keyword: Biomass, diameter, sengon, soil carbon